ANALISIS RASIO KEUANGAN TERHADAP TINGKAT PERTUMBUHAN LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Resihono, Legowo Dwi (Universitas Of Surakarta, 2021)
This study aims to determine and analyze financial ratios to the level of profit growth in pharmaceutical companies lied on the IDX in 2014-2018. Financial ratio used in this study are the quick ratio, debt to equity ratio, net profit margin, and total asset turnover as an independent variable, then profit growth as a variable bound. This research includes quantitative research. Methods of data collection carried out is documentation through secondary data, namely the financial statements of pharmaceutical companies on the website the official Indonesian Stock Exchange and IDN Financial. This study uses a population of consumer goods industry companies in the pharmaceutical sector which totaling 10 companies with a sample of 7 companies obtained through purposive sampling. The analysis used to conduct this research is by conducting a test classical assumptions, multiple linear regression, hypothesis testing and coefficient of determination test. Research resultpartially the QR variable has a significant effect, the DER variable has no significant effect, the NPM variable has a significant effect and the TATO variable has no significant effect on profit growth rate. Meanwhile, simultaneously the financial ratios used in This study has a significant effect on the rate of profit growth.